Ecological testing of different selective numbers of meadow clover in the Smolensk region - O. V. Kurdakova; E. S. Rekashus (Аграрная наука Евро-Северо-Востока)
Prospective selective material of the double-cut diploid meadow clover (Trifolium pratense L.) was tested. The aim of the research was to identify selective numbers mostly adapted to the ecological conditions of the Smolensk region. Six selective numbers were tested: №23 (Belarusian State Agricultural Academy), №28 (Kotlas Experimental Station, Arkhangelsk Region), № 38 (Falenki Breeding Station, Kirov region), GP-10-93 (Federal Agricultural Research Center of the North-East named N.V. Rudnitsky), №15-6-D and №440 (Federal Williams Research Center for Feed Production and Agroecology). Variety Nadezhny, which has been in the State Register of Selection Achievements since 2012, was the standard. The testing was carried out in 2012-2015 in plant breeding crop rotation on the sod mesopodzol light loamy soil. The weather conditions were favorable with increased temperature and optimal soil moisture. The selective number №23 from the Republic of Belarus has been chosen. On the average, over the three cycles of research it surpassed the standard Nadezhny by 8.4% in winter hardiness, by 23.7% in green mass yield, by 24.4% in hay yield, by 26.9% in seed yield. This selection number was the most adaptive to the conditions of the Smolensk region. It has been recommended for passing the state varietal testing.